2018
DOI: 10.1016/j.ultsonch.2018.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ultrasound application and NaCl concentrations on brining kinetics and textural properties of Chinese cabbage

Abstract: The effects of ultrasound application on the brining kinetics of Chinese cabbage leaves was evaluated at different NaCl concentrations (10, 15, and 20%) of the brine, and its influence on textural properties and salt distribution was also investigated. To identify the effects of these two factors on water and NaCl fluxes, the kinetics of transport was analyzed by taking the diffusion theory into account. The results showed that NaCl concentration and ultrasound application significantly affected moisture and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 29 publications
1
21
0
2
Order By: Relevance
“…The brining kinetics parameters of k 1 and k 2 at an ultrasonic intensity of 7.5 W/cm 2 were close to those of the control, which might be explained by the two brining method involved different mechanisms during brining process. Actually, k 1 describes the change at the beginning of the brining process, and k 2 is related to the kinetics of diffusion mechanism in terms of process yield (Du, Zhou, Xu, & Li, ; Leng, Zhang, Huang, Xu, & Zhou, ; Zhao & Eun, ). The fitting correlation factors ( R 2 > .9) of the model for different treatment condition indicated that the mass transfer kinetics model could predict the changes of beef weight during brining process.…”
Section: Resultsmentioning
confidence: 99%
“…The brining kinetics parameters of k 1 and k 2 at an ultrasonic intensity of 7.5 W/cm 2 were close to those of the control, which might be explained by the two brining method involved different mechanisms during brining process. Actually, k 1 describes the change at the beginning of the brining process, and k 2 is related to the kinetics of diffusion mechanism in terms of process yield (Du, Zhou, Xu, & Li, ; Leng, Zhang, Huang, Xu, & Zhou, ; Zhao & Eun, ). The fitting correlation factors ( R 2 > .9) of the model for different treatment condition indicated that the mass transfer kinetics model could predict the changes of beef weight during brining process.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, when the brining process reaches equilibrium, the NaCl concentration of the liquid phase of cabbage leaves is equal to the concentration of NaCl of the brining solution (y N e ) (Zhao & Eun, 2018). The theoretical equilibrium value was calculated using the initial Chinese cabbage brining solution ratio (…”
Section: Total Water and Nacl Weight Changes Of Chinese Cabbage Durmentioning
confidence: 99%
“…The diffusion coefficient calculated by the Fick's second law has been commonly used to evaluate the mass transfer of food during brining process (Du, Zhou, Xu, & Li, 2010; Zhao & Eun, 2018). Volpato, Michielin, Ferreira, and Petrus (2007) estimated the amount of NaCl absorbed in chicken breast during curing process.…”
Section: Introductionmentioning
confidence: 99%